The Shielding of CEO Compensation from the Effects of Strategic Expenditures* - Duru, Augustine; Iyengar, Raghavan J.; Thevaranjan, Alex (Contemporary Accounting Research, 2002)
This study investigates whether and why compensation committees shield CEO compensation from income‐decreasing effects of strategic expenditures. We document that firms do shield recurring strategic expenditures such as research and development and advertising expenditures. We also find that firms shield research and development expenditures more than advertising expenditures. Our results are consistent with prior findings that suggest that compensation committees shield CEOs from nonroutine transactions such as restructuring charges and extraordinary losses. Using a two‐task principal‐agent framework, we show that such shielding improves the efficiency of the contract by making the shielded income measure more congruent with the principal's objectives.